Connecting Students' Interests to a Learning Context: The Case of Ecosystem Services in STEM Education - Elena A. Mikhailova; Christopher J. Post; Grayson L. Younts; Mark A. Schlautman (MDPI AG, 2022)
Interest in a subject matter is a powerful motivation in education. Prior knowledge of students' interests can be helpful in teaching the concept of ecosystem services (ES) and disservices (ED), which is increasingly being used in science, technology, engineering, and mathematics (STEM) education, including soil science. Study objectives were to evaluate prior students' soil science-related interests and use them to expand the learning context of a laboratory exercise on soil reaction (pH) with ES/ED in an online introductory soil science course (FNR 2040: Soil Information Systems) taught at Clemson University. Students from multiple fields of study (environmental and natural resources, forestry, and wildlife biology) completed the laboratory exercise in Fall 2021. This exercise on soil regulating and provisioning ES/ED included a sequence of reusable learning objects (RLOs), which are self-contained online modules frequently used for e-learning. Laboratory activities included calculating the liming replacement cost of soil inorganic carbon (SIC) and avoided social cost of carbon (SC-CO2) from soil inorganic carbon (SIC) stocks in the assigned soil. The laboratory exercise was effective in increasing the familiarity with the concept of ES/ED (+39.4 increase in "extremely familiar" category) and the concept of SIC (+44.7 increase in "moderately familiar" category). The graded online quiz consisted of 9 questions and was taken by 55 students with an average score of 7.0 (out of 9). A post-assessment survey found that the laboratory was an effective way to learn about soil pH, SIC, and their ES/ED. Detailed student comments showed learning enjoyment (e.g., calculations, good experience), the value of multimedia (e.g., video, PowerPoint), the learning flexibility (e.g., separate parts), content applicability (e.g., economic values of services), and constructive criticism (e.g., clearer instructions, lots of information). A word cloud based on comments by the students about their soil ES laboratory exercise experience indicated the most common words submitted by students to describe their experience, such as "soil", "calculations", "enjoyed", "learning", and "values", among others. Applied recommendations are proposed to develop future exercises based on the alignment of students' interests, STEM subject matter, and ES/ED applications.